Humanitarianism, Sovereignty, and ASEAN Mode of Governance: Another Perspective from the Global South - Sutrisno, Nandang (Animo Repository, 2019)
As the world has become increasingly more connected, the nature of humanitarian problems has also become transnational. To confront them, as a consequence, international cooperation is inevitably needed. In particular, the ongoing Rohingya crisis is the latest example that showcases the state-centered model of ASEAN (or the Southeast Asian) model of regional cooperation that has failed in the area of humanitarian management. Furthermore, it suggests that ASEAN has abandoned the very purpose of its existence as it was conceived in its founding document, the Bangkok Declaration. Against this background, this paper argues that the region’s failure cannot be separated from the region’s rigid understanding of the notion of state sovereignty. Analytically speaking, this paper claims that the current conservative interpretation has significantly contributed to the dampening of the supposedly liberating nature of ASEAN. Thus, it is fair that this requires a healthy dose of a more progressive direction in the region’s interpretation of within ASEAN. Moreover, this paper suggests that, should the region take a more progressive turn in its understanding of humanitarianism, it is highly plausible to transform the (conservative) Bangkok Declaration itself as starting point that necessitates “a primary responsibility” among its member states with regard to the advancement and protection of human values in the region and beyond. Given the current worldwide race among the nations to the bottom of ultra-nativism, this could be a fresh start for the region, and ASEAN in particular, to emerge as a leading champion of humanity.